Penggunaan Media Counting Box sebagai Perwujudan dari Teori Bruner Untuk Meningkatkan Pemahaman Materi Pengurangan pada Siswa Kelas 1 SD Negeri Podorejo 03 - Yunita Fitri Yaningsih; Fajar Aunurofiq; Ika Rizqi Ariyani; Shanti Putri Kirani; Tri Muliani; Nurhayati N; Trimurtini T (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this study was to improve students' understanding of whole number operations in elementary school mathematics by applying Bruner's theory through the counting box game. The study was conducted at SD Negeri Podorejo 03 Semarang with a population of first-grade students. The method used was qualitative description so that the researcher could understand the actual classroom situation and how first-grade students at SD Negeri Podorejo 03 understood the subtraction of numbers 1 to 20 correctly and clearly. The instruments used were interviews and tests conducted orally and in writing after applying the counting box game. The results of the study showed that 14 students scored above the KKM, while 2 students scored below the KKM. Based on this, it can be concluded that counting box-based learning media can improve students' understanding of the subtraction of numbers 1 to 20 by applying Bruner's theory through counting box learning media, which makes the classroom more active, learning more meaningful, and the classroom more interactive.